Application of Realistic Mathematics Education (RME) To Improve The Students’ Mathematical Communication Ability - Irham Habibi Harahap; Dwi Novita Sari (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
This article will discuss the communication skills of SMP IT Al Ikhwan students in class VII-1 and VII-2 each with a total of 32 students, after being given learning through RME. Determination of the sample is done by simple random. The research instrument used in this study was a test that was statistically analyzed using N-Gain. After carrying out a series of activities starting from the pretest, treatment and posttest, it can be concluded that the use of RME was apparently good for improving mathematical communication skills as seen from the N-Gain acquisition for each class that was sampled. The learning process that uses RME opens opportunities for students to be able to play a more active role in expressing themselves in solving mathematical problems and realistic mathematics education gets a very good response, students really like it and feel very excited.